1999
DOI: 10.1046/j.1525-1594.1999.06110.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation After Valve Replacement: A Multicenter Retrospective Study

Abstract: Anticoagulant therapy after cardiac valve replacement was evaluated retrospectively in 1,200 patients attending 8 cardiac surgery clinics in the Tokyo area as part of the Tokyo Area Study on Anticoagulation After Cardiac Valve Replacement Using PT-INR (TAS). A prospective trial is also in progress and will be reported later. The prothrombin time international normalized ratio (PT-INR) was determined at the time of thromboembolic and bleeding complications in 1,200 patients. During the 5 year study period, thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…You et al [8] reported that INR of 1.8-2.4 appeared to be associated with the lowest incidence rate of major bleeding or thromboembolic events in a cohort of Hong Kong Chinese patients receiving warfarin therapy for moderateintensity anticoagulation. However, Tatsuhiko et al [9] reported thromboembolism in 71% of patients and bleeding complications in 47% patients on INR ranging from 1.6 to 2.8.…”
Section: Discussionmentioning
confidence: 99%
“…You et al [8] reported that INR of 1.8-2.4 appeared to be associated with the lowest incidence rate of major bleeding or thromboembolic events in a cohort of Hong Kong Chinese patients receiving warfarin therapy for moderateintensity anticoagulation. However, Tatsuhiko et al [9] reported thromboembolism in 71% of patients and bleeding complications in 47% patients on INR ranging from 1.6 to 2.8.…”
Section: Discussionmentioning
confidence: 99%
“…7 Asians seem to be less vulnerable to thrombotic diseases than Caucasians. The incidence of thromboembolism is low in Japan, despite the less intensive regimen; 2,3,8 however, guidelines for the optimal therapeutic range do not exist in Japan. Kitamura et al recommend an optimum range for the INR between 1.2 and 3.0 in patients with a low risk of thromboembolism, and between 2.0 and 3.0 in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, low‐intensity anticoagulation is suggested to most Asian patients because they would suffer higher frequency of bleeding than their Caucasian counterparts . However, some Asian patients may need high‐intensity anticoagulation due to several thrombophilia factors . These potential risks cannot be identified by INR test alone; therefore, supplemental markers are needed to improve individualized anticoagulation.…”
Section: Use Of D‐dimer In Oral Anticoagulation Therapymentioning
confidence: 99%
“…44,48 However, some Asian patients may need high-intensity anticoagulation due to several thrombophilia factors. 4,49 These potential risks cannot be identified by INR test alone; therefore, supplemental markers are needed to improve individualized anticoagulation. D-dimers can screen out patients with inadequate anticoagulation.…”
Section: Use Of D-dimer To Guide the Optimal Intensity Of Anticoagumentioning
confidence: 99%